BMC Molecular Biology
BMC Molecular Biology is an open access journal publishing original peer-reviewed research articles in all aspects of DNA and RNA in a cellular context, encompassing investigations of chromatin, replication, recombination, mutation, repair, transcription, translation and RNA processing and function.